2013
DOI: 10.1111/1462-2920.12189
|View full text |Cite
|
Sign up to set email alerts
|

From models to pathogens: how much have we learned aboutStreptococcus pneumoniaecell division?

Abstract: SummaryStreptococcus pneumoniae is an oval-shaped Grampositive coccus that lives in intimate association with its human host, both as a commensal and pathogen. The seriousness of pneumococcal infections and the spread of multi-drug resistant strains call for new lines of intervention. Bacterial cell division is an attractive target to develop antimicrobial drugs. This review discusses the recent advances in understanding S. pneumoniae growth and division, in comparison with the best studied rod-shaped models, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
228
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(235 citation statements)
references
References 222 publications
7
228
0
Order By: Relevance
“…Markerless deletions of the division genes, mapZ (alternative name, locZ) and divIVA, fused short (20-amino acid) stretches from the beginning and end of the genes to maintain possible translational coupling (see Tables S1 and S2). The phenotypes of the markerless ⌬mapZ and ⌬divIVA mutants were similar to those reported previously for other mapZ and divIVA mutants (41)(42)(43).…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Markerless deletions of the division genes, mapZ (alternative name, locZ) and divIVA, fused short (20-amino acid) stretches from the beginning and end of the genes to maintain possible translational coupling (see Tables S1 and S2). The phenotypes of the markerless ⌬mapZ and ⌬divIVA mutants were similar to those reported previously for other mapZ and divIVA mutants (41)(42)(43).…”
Section: Methodssupporting
confidence: 86%
“…8, top row). Finally, we examined the PG stability in a ⌬pbp1a mutant lacking the major class A PBP1a, which likely functions in both septal and peripheral (i.e., midcell sidewall) PG synthesis (43,76). ⌬pbp1a mutants have the distinctive phenotype of forming considerably smaller but normally shaped cells compared to their pbp1a ϩ parent strain (Fig.…”
Section: Figmentioning
confidence: 99%
“…Perhaps more importantly, the spatial and temporal regulation of PG synthesis contributing to either cell elongation or septum formation are vastly different between B. burgdorferi and S. pneumoniae, ultimately shaping their cell morphology. In S. pneumoniae, cell elongation occurs at the same time and place as septum formation, such that cells adopt a prolate spheroid shape (6,(25)(26)(27)(28)(29). This is in contrast to B. burgdorferi, in which cell elongation and septum formation are largely uncoupled, resulting in long, rod-shaped cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have clearly indicated that the divisome of E. coli (50), S. pneumoniae (51), and S. aureus (49) are built by a complex network of interactions where each component interacts with multiple partners. By homology search, we identified the GAS counterpart of most genes involved in division of S. pneumoniae (see Table S4 in the supplemental material) and we predict that, in addition to FtsZ, SpyAD possibly interacts with other components of the GAS cell division apparatus and/or the peptidoglycan synthesis machinery located in the septum of Gram-positive cocci (52,53). Indeed, SpyAD shares structural features of many divisome interacting proteins including coiled-coil arrangements and a leucine zipper motif.…”
Section: Discussionmentioning
confidence: 99%